Childhood onset C3 glomerulopathy: recurrence after kidney transplantation—a case series - Borovitz, Yael; Landau, Daniel; Dagan, Amit; Alfandari, Hadas; Haskin, Orly; Levi, Shelly; Hamdani, Gilad; Levy Erez, Daniella; Tzvi-Behr, Shimrit; Weinbrand-Goichberg, Jenny; Tobar Foigelman, Ana; Rahamimov, Ruth (Frontiers in Pediatrics, 2024)
Background: C3 Glomerulopathy (C3G) is a complement-mediated disease, with predominant C3 deposits, where pathogenic genetic variants in complement system components and circulating autoantibodies result in loss of control of the alternative pathway, have been described. A high incidence of disease recurrence including graft failure has been reported after kidney transplantation (KTx). Currently treatment modalities for preventing and treating post KTx C3G recurrence (plasma exchange, rituximab and eculizumab) in adults have yielded inconsistent results. Data on post KTx C3G recurrence in childhood-onset C3G is still unknown. Methods: A comprehensive case study of patients diagnosed with C3G as children or adolescents, who underwent KTx between the years 2015-2023. Data collected included complement workup, treatment modalities, and outcomes. Results: 19 patients with C3G were identified during the study period. Five patients developed ESRD and received a kidney transplant. C3G recurrence was diagnosed post KTx in 100% of patients. Graft function improved in 3 of these patients (two with anti-factor H antibodies) after eculizumab treatment, one patient reached graft failure 9 months after transplantation despite eculizumab, received a second successful transplantation with pre-emptive eculizumab treatment and one patient showed histologic signs of disease recurrence without clinical signs. Conclusions: C3G recurrence after KTx in patients diagnosed as children or adolescents may be higher than previously described. Treatment with eculizumab is beneficial in some patients. New treatments are needed for improving post-transplant outcome in patients with C3G.